2009
DOI: 10.1093/toxsci/kfp271
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Exposure to Triclosan Decreases Thyroxine In Vivo via Upregulation of Hepatic Catabolism in Young Long-Evans Rats

Abstract: Triclosan (5-chloro-2-(2,4-dichlorophenoxy)-phenol) is a chlorinated phenolic antibacterial compound found in consumer products. In vitro human pregnane X receptor activation, hepatic phase I enzyme induction, and decreased in vivo total thyroxine (T4) suggest adverse effects on thyroid hormone homeostasis. Current research tested the hypothesis that triclosan decreases circulating T4 via upregulation of hepatic catabolism and transport. Weanling female Long-Evans rats received triclosan (0-1000 mg/kg/day) by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
111
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(124 citation statements)
references
References 70 publications
11
111
2
Order By: Relevance
“…Recent studies have shown that triclosan is able to induce antibiotic resistances in various bacteria stems [43], to accumulate in human milk samples and in fish exposed to municipal wastewater [44], to be found in biosolids which might be spread on agricultural land (also causing adverse effects in the soil environment [45]) and to reduce serum thyroid hormone levels following oral administration [46]. Due to these findings, concerns about the use of triclosan have been raised.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that triclosan is able to induce antibiotic resistances in various bacteria stems [43], to accumulate in human milk samples and in fish exposed to municipal wastewater [44], to be found in biosolids which might be spread on agricultural land (also causing adverse effects in the soil environment [45]) and to reduce serum thyroid hormone levels following oral administration [46]. Due to these findings, concerns about the use of triclosan have been raised.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on other aquatic vertebrates such as frogs have shown that environmentally relevant levels of triclosan can disrupt the expression profile of thyroid hormone receptors (Veldhoen et al, 2006) and the expression of TR␣ (Fort et al, 2009). Studies on rats showed no significant effects of triclosan on thyroid histology (Zorrilla et al, 2009) or thyroid mass (Axelstad et al, 2013) but they revealed a consistent dose-dependent decline in serum T4 whereas the decrease in serum T3 was less pronounced (Axelstad et al, 2013;Crofton et al, 2007;Paul et al, 2009;Stoker et al, 2010;Zorrilla et al, 2009). These studies suggest that the brain-pituitary-thyroid axis that regulates T4 biosynthesis and secretion is not affected by triclosan exposure.…”
Section: Effect Of Triclosan On Variation Of Thyroid Hormones In Devementioning
confidence: 99%
“…The first study to indicate that triclosan is capable of inhibiting sulfation of thyroid hormones was performed by Schuur et al, 1998, who studied the in vitro inhibition of diiodothyronine (T2) sulfotransferase activity using rat liver cytosol (Schuur et al, 1998). Studies on rats gavaged with triclosan revealed an increased T4-glucuronidation activity (Paul et al, 2009;Zorrilla et al, 2009). The contribution of other mechanisms of triclosaninduced thyroid hormone deficiency, such as impaired deiodinase activity or competitive binding to thyroid hormone serum proteins, have been even less explored (Butt et al, 2011).…”
Section: Effect Of Triclosan On Variation Of Thyroid Hormones In Devementioning
confidence: 99%
“…A mode of action involved activations of pregnane X receptor (PXR) and constitutive androstane receptor (CAR), which induced activities of hepatic phases I and II enzymes and ultimately increased clearance of THs from the body [6]. Moreover, the study also reported that triclosan could accelerate the biliary excretion of THs through inducing TH sulfation [6].…”
Section: Introductionmentioning
confidence: 99%